Intermediate algebra - Larson, Ron
Designed for first-year developmental math students who need support in intermediate algebra, the Fourth Edition of Intermediate Algebra owes its success to the hallmark features for which the Larson team is known: learning by example, accessible writing style, emphasis on visualization, and comprehensive exercise sets. These pedagogical features are carefully coordinated to ensure that students are better able to make connections between mathematical concepts and understand the content. The new Student Support Edition continues the Larson tradition of guided learning by incorporating a comprehensive range of student success materials throughout the text. Additionally, instructors and students alike can track progress with HM Assess, a new online diagnostic assessment and remediation tool from Houghton Mifflin